Water quality assessment of streams and rivers for irrigation in Southern Continental Patagonia = Evaluación de la calidad del agua para irrigación en ríos y arroyos de la Patagonia Austral Continental - Diaz, Boris Gaston (2025)
This work aimed to analyze and classify the suitability of freshwater sources for irrigation in three large hydrographic regions of Southern Continental Patagonia: Coyle, Serrano, and Gallegos. In these regions, there is a lack of information on the irrigation suitability of surface waters. For this, 74 surface water locations were sampled from 42 watercourses in Santa Cruz province and Magallanes region in Argentina and Chile, during dry and wet seasons between 2017 and 2019. The concentration of ions of agricultural interest was evaluated in the laboratory. The pH ranged between 6.1-9.5 with little seasonal variability. The prevailing ions were Ca2+ Mg2+ and HCO3-, while the lower cation concentration was K+. The Sodium Adsorption Ratio was 0.58 ± 0.21 during winter and 0.46 ± 0.15 in summer. Most waters in the region have electrical conductivity values below 250 µS/cm and may be categorized as low-salinity waters. We determined no significant hazards for crops, vegetables, and pasture production in terms of the combined salinity and sodicity indicators. However, a potential negative impact on soil structural stability mainly due to Na+ concentration must be considered for the implementation of suitable irrigation projects.